Associations between ASA Physical Status and postoperative mortality at 48 h: a contemporary dataset analysis compared to a historical cohort. Issue 1 (December 2016) - Hopkins, Thomas; Raghunathan, Karthik; Barbeito, Atilio; Cooter, Mary; Stafford-Smith, Mark; Schroeder, Rebecca; Grichnik, Katherine; Gilbert, Richard; Aronson, Solomon
Abstract Background In this study, we examined the association between American Society of Anesthesiologists Physical Status (ASA PS) designation and 48-h mortality for both elective and emergent procedures in a large contemporary dataset (patient encounters between 2009 and 2014) and compared this association with data from a landmark study published by Vacanti et al. in 1970. Methods Patient history, hospital characteristics, anesthetic approach, surgical procedure, efficiency and quality indicators, and patient outcomes were prospectively collected for 732, 704 consecutive patient encounters between January 1, 2009, and December 31, 2014, at 233 anesthetizing locations across 19 facilities in two US states and stored in the Quantum™ Clinical Navigation System (QCNS) database. The outcome (death within 48 h of procedure) was tabulated against ASA PS designations separately for patients with and without "E" status labels. To maintain consistency with the historical cohort from the landmark study performed by Vacanti et al. on adult men at US naval hospitals in 1970, we then created a comparison cohort in the contemporary dataset that consisted of 242, 103 adult male patients (with/without E designations) undergoing elective and emergent procedures. Differences in the relationship between ASA PS and 48-h mortality in the historical and contemporary cohorts were assessed for patients undergoing elective and emergent procedures. Results As reported nearly five decades ago, we found a significant trend toward increased mortality with increasing ASA PS for patients undergoing both elective and emergent procedures in a large contemporary cohort (p < 0.0001). Additionally, the overall mortality rate at 48 h was significantly higher among patients undergoing emergent compared to elective procedures in the large contemporary cohort (1.27 versus 0.03 %, p < 0.0001). In the comparative analysis with the historical cohort that focused on adult males, we found the overall 48-h mortality rate was significantly lower among patients undergoing elective procedures in the contemporary cohort (0.05 % now versus 0.24 % in 1970, p < 0.0001) but not significantly lower among those undergoing emergent procedures (1.88 % now versus 1.22 % in 1970, p < 0.0001). Conclusions The association between increasing ASA PS designation (1–5) and mortality within 48 h of surgery is significant for patients undergoing both elective and emergent procedures in a contemporary dataset consisting of over 700, 000 patient encounters. Emergency surgery was associated with a higher risk of patient death within 48 h of surgery in this contemporary dataset. These data trends are similar to those observed nearly five decades ago in a landmark study evaluating the association between ASA PS and 48-h surgical mortality on adult men at US naval hospitals. When a comparison cohort was created from the contemporary dataset and compared to this landmark historical cohort, the absolute 48-h mortality rate was significantly lower in the contemporary cohort for elective procedures but not significantly lower for emergency procedures. The underlying implications of these findings remain to be determined.